PERANAN GURU DALAM MEMBENTUK KARAKTER DISIPLIN SISWA SMA NEGERI TUAH KEMUNING KELURAHAN SELENSEN KECAMATAN KEMUNING - Awanda Fildini; Hambali Hambali; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrack : Character education is not a new term in the field of education because at this time character education already exists in all subjects with the aim of fostering the character and character of students. Teachers are required to be able to integrate all the main character values contained in each of these subjects, in the learning process starting from the planning, implementation and evaluation stages of learning which from day to day need to be designed and implemented to support the formation of student disciplinary character. This research was conducted to determine the role of teachers in shaping the character of student discipline in SMA Negeri Tuah Kemuning. Based on this background, the problem that arises is how the role of the teacher in shaping the disciplinary character of Tuah Kemuning Senior High School students? The purpose of this study was to determine the role of the teacher in shaping the disciplinary character of the students of SMA Negeri Tuah Kemuning. In this study the writer will present the data which is the result of the research conducted by the author at SMA Negeri Tuah Kemuning, where this research uses observation data collection techniques, interviews, and questionnaires. In this study, a sample of 28 teachers of SMA Negeri Tuah Kemuning as respondents to fill out a research questionnaire. The results of this study were analyzed using quantitative descriptive analysis techniques. Based on the results of the study, it was found that the results of the average percentage value of the alternative answers to the dominant respondents were 62.08% where this range was in the "Good" category with the presence in the range 50.01-75%. Thus the role of teachers in disciplinary character education of students at SMA Negeri Tuah Kemuning is good.Key Word :Role of Teacher, Character of Discipline